Forecasting Future Crime Rates - Rosenfeld, Richard (Journal of contemporary criminal justice, 2024)
Despite its importance for testing criminological theories and informing crime control policy, forecasting crime rates has all but disappeared from criminology. We argue for a resurgence of crime forecasting in the study of crime trends. As an example of the value, as well as the challenges, of forecasting, we engage in a forecasting exercise based on data from New York City. We discuss each of the steps taken to forecast New York’s violent and property crime rates to 2024, from preparing the data for reliable analysis, specifying the forecasting model, selecting the forecasting method, and validating the results. The results of autoregressive integrated moving average (ARIMA) forecast models show a rise in New York’s violent and property crime rates in 2022 and 2023 before flattening in 2024. Renewed attention to forecasting can help to secure the future of the study of crime trends.